Incidence and mortality trends in oral and oropharyngeal cancers in China, 2005–2013. (December 2018) - Zhang, Li-Wei; Li, Jin; Cong, Xin; Hu, Xiao-Sheng; Li, Dan; Wu, Li-Ling; Hua, Hong; Yu, Guang-Yan; Kerr, Alexander Ross
Highlights: The incidence of oral and oropharyngeal cancers fluctuated, whereas the mortality increased from 2005 to 2013 in China. A heavier burden from oral and oropharyngeal cancers was predicted in the next two decades in China. This is the latest summarization of the epidemiological trends of oral and oropharyngeal cancers in China. Abstract: Background: Oral and oropharyngeal cancers are among the most common cancers globally. This study aimed to assess the incidence and mortality trends of oral and oropharyngeal cancers in China between 2005 and 2013. Methods: Estimates of national trends of oral and oropharyngeal cancers were based on the data from Chinese Cancer Registry Annual Reports. The crude incidence rates of oral and oropharyngeal cancers between 2015 and 2035 were evaluated. The age-standardized rate was based on the world standard population. Results: It was estimated that 285, 857 new cases and 132, 698 deaths were related to oral and oropharyngeal cancers in China between 2005 and 2013, with mouth and tongue cancers being the most frequently diagnosed and the leading causes of death among all oral and oropharyngeal cancers. The incidence rates of oral and oropharyngeal cancer fluctuated from 1.69 to 1.89 per 100, 000 person-years, and the mortality rate showed an increasing trend, ranging from 0.77 and 0.84 per 100, 000 person-years. Males were more susceptible than females to oral and oropharyngeal cancers. The incidence and mortality rates of oral and oropharyngeal cancers were significantly higher in urban regions. The crude incidence rates of oral cancers are projected to increase from 2.26 to 3.21 per 100, 000 person-years over the next 20 years in China. Conclusion: The incidence of oral and oropharyngeal cancers fluctuated, whereas the mortality rate showed an upward trend from 2005 to 2013. A heavier burden from oral and oropharyngeal cancers is predicted in the next two decades in China.